Productive performance, egg quality and bone characteristics of quails fed with meal and canola oil - Priscila de Oliveira Moraes; Edenilse Gopinger; Caroline Bavaresco; Aiane Aparecida da Silva Catalan; Renata Cedres Dias; Eduardo Gonçalves Xavier (Acta Scientiarum. Animal Sciences, 2017)
This study evaluated the effect of canola meal and oil in quail diet on productive performance, egg quality and bone characteristics. Quails (n = 84) with 150-days-of-age and average weight of 234±17 g were used in this experiment that lasted 84 days. The experiment consisted of a completely randomized design with 4 treatments, 7 replications with 3 birds each. Four diets were formulated: SM+SO - control diet with soybean meal and oil; MC+SO - 25% replacement of soybean meal with canola meal; MC+CO - 25% replacement of soybean meal with canola meal and complete replacement of canola oil with soybean oil; SM+OC - control diet with soybean meal and canola oil. Productive performance, internal and external egg quality and bone characteristics were evaluated. The diet with canola meal and oil (MC+CO) decreased (p <0.05) feed conversion. Albumen height was lower (p < 0.05) for treatments with canola meal and oil (MC+CO). Regardless of the oil used, the dietary canola meal (MC+SO and MC+CO) reduced the weight and length of tibia (p < 0.05), but increased its ash content (p < 0.05). The mixture of canola oil and meal decreases feed conversion, and negatively affects internal egg quality and bone characteristics of quails.